The scope of carer effects and their inclusion in decision-making: a UK-based Delphi study - Hareth Al-Janabi; Nikolaos Efstathiou; Carol McLoughlin; Melanie Calvert; Jan Oyebode (BMC, 2021)
Abstract Background and objective Health and social care may affect unpaid (family) carers' health and wellbeing in addition to patients' lives. It is recommended that such impacts (carer effects) are considered in decision-making. However, the scope of carer effects and range of decisions where carer effects should be considered is uncertain. This study aimed to identify: (i) how different categories of healthcare and social care were perceived to impact on unpaid carers; and (ii) whether there was consensus about when carer effects should be formally considered in decision-making contexts. Methods A two round, online Delphi study was conducted with 65 UK-based participants (unpaid carers, care professionals, and researchers) with expertise in dementia, mental health, and stroke. Participants considered two broad forms of 'interventions' (patient treatment and replacement care) and two broad forms of 'organisational change' (staffing and changes in timing/location of care). Participants assessed the likely impacts of these on unpaid carers and whether impacts should be considered in decision-making. Results Participants predicted interventions and organisational changes would impact on multiple domains of unpaid carers' lives, with 'emotional health' the most likely outcome to be affected. Patient treatment and replacement care services ('interventions') were associated with positive impacts across all domains. Conversely, timing/location changes and staffing changes ('organisational changes') were perceived to have mixed and negative impacts. There was widespread support (80-81 %) for considering carer effects in research studies, funding decisions, and patient decision-making. Conclusions This study highlights a perception that carer effects are widespread and important to consider in economic evaluation and decision-making. It highlights the particular need to measure and value effects on carers' emotional health and the need to use a societal perspective to avoid cost shifting to unpaid carers when introducing interventions and making organisational changes.